Typical and Atypical Development of Visual Expertise for Print as Indexed by the Visual Word N1 (N170w): A Systematic Review - Amora, Kathleen Kay; Tretow, Ariane; Verwimp, Cara; Tijms, Jurgen; Leppänen, Paavo H. T.; Csépe, Valéria (Frontiers in Neuroscience, 2022)
The visual word N1 (N170w) is an early brain ERP component that has been found to be a neurophysiological marker for print expertise, which is a prelexical requirement associated with reading development. To date, no other review has assimilated existing research on reading difficulties and atypical development of processes reflected in the N170w response. Hence, this systematic review synthesized results and evaluated neurophysiological and experimental procedures across different studies about visual print expertise in reading development. Literature databases were examined for relevant studies from 1995 to 2020 investigating the N170w response in individuals with or without reading disorders. To capture the development of the N170w related to reading, results were compared between three different age groups: pre-literate children, school-aged children, and young adults. The majority of available N170w studies (N = 69) investigated adults (n = 31) followed by children (school-aged: n = 21; pre-literate: n = 4) and adolescents (n = 1) while some studies investigated a combination of these age groups (n = 12). Most studies were conducted with German-speaking populations (n = 17), followed by English (n = 15) and Chinese (n = 14) speaking participants. The N170w was primarily investigated using a combination of words, pseudowords, and symbols (n = 20) and mostly used repetition-detection (n = 16) or lexical-decision tasks (n = 16). Different studies posed huge variability in selecting electrode sites for analysis; however, most focused on P7, P8, and O1 sites of the international 10–20 system. Most of the studies in adults have found a more negative N170w in controls than poor readers, whereas in children, the results have been mixed. In typical readers, N170w ranged from having a bilateral distribution to a left-hemispheric dominance throughout development, whereas in young, poor readers, the response was mainly right-lateralized and then remained in a bilateral distribution. Moreover, the N170w latency has varied according to age group, with adults having an earlier onset yet with shorter latency than school-aged and pre-literate children. This systematic review provides a comprehensive picture of the development of print expertise as indexed by the N170w across age groups and reading abilities and discusses theoretical and methodological differences and challenges in the field, aiming to guide future research. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021228444.